A Comprehensive Framework for Evaluating the Scalability and Security of Fintech Web Applications in a Cloud-Native Environment - Sai Teja Battula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for evaluating and designing cloud-native fintech applications that balance scalability requirements with robust security postures. As financial institutions increasingly migrate to cloud environments, they face complex challenges at the intersection of technological innovation, regulatory compliance, and cybersecurity. The article examines core architectural considerations, including scalability patterns like microservices and event-driven design, alongside essential security frameworks such as zero-trust architecture and defense-in-depth strategies. It explores cloud-native deployment approaches through container orchestration and serverless architectures while addressing specific challenges related to latency management, multi-tenancy considerations, and data sovereignty requirements. The article provides systematic metrics for assessing fintech architectures across three critical dimensions: scalability metrics to measure performance under varying conditions, security posture evaluations to ensure comprehensive threat mitigation and operational excellence indicators to maintain service reliability. It enables financial institutions to build resilient, compliant, and efficient cloud-native applications that adapt to evolving market demands and regulatory landscapes.